2013
DOI: 10.3109/21678421.2013.812659
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of percutaneous endoscopic gastrostomy insertion in patients with amyotrophic lateral sclerosis in relation to respiratory dysfunction

Abstract: Our objective was to describe a group of ALS patients who underwent percutaneous endoscopic gastrostomy (PEG) insertion, with emphasis on the respiratory function, by comparing patients with forced vital capacity (FVC) > 30% versus FVC ≤ 30%, and the effect of respiratory dysfunction on the perioperative complication rate and survival. Thirty consecutive ALS patients in whom FVC status was known underwent PEG insertion at our centre. Twenty of them had FVC > 30% (50.1% ± 20) at the time of the procedure, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 27 publications
4
20
0
Order By: Relevance
“…Other reported prognostic factors that influence PEG outcome include low serum cholesterol level, low lymphocyte count, hyponatremia, and severe comorbidity such as cardiovascular disease [17,33,34]. Although one study reported that FVC <65% is a predictor of poor outcome in MND patients [14], no excess morbidity and mortality were reported in other studies in MND patients whose FVC prior to PEG tube insertion is <50% predicted [8,19,20,35]. One group reported that periprocedural non-invasive ventilation (NIV) may minimize risk of PEG tube placement in subjects with FVC <50% [19], and the ESPEN guidelines recommended that PEG tube placement be considered prior to the FVC falling below 50% predicted [3].…”
Section: Discussionmentioning
confidence: 99%
“…Other reported prognostic factors that influence PEG outcome include low serum cholesterol level, low lymphocyte count, hyponatremia, and severe comorbidity such as cardiovascular disease [17,33,34]. Although one study reported that FVC <65% is a predictor of poor outcome in MND patients [14], no excess morbidity and mortality were reported in other studies in MND patients whose FVC prior to PEG tube insertion is <50% predicted [8,19,20,35]. One group reported that periprocedural non-invasive ventilation (NIV) may minimize risk of PEG tube placement in subjects with FVC <50% [19], and the ESPEN guidelines recommended that PEG tube placement be considered prior to the FVC falling below 50% predicted [3].…”
Section: Discussionmentioning
confidence: 99%
“…One first reason was linked to European and North American Guidelines that cautiously advise to consider the riskbenefit imbalance before proposing gastrostomy to ALS patients with severe respiratory failure [10,11] . However, since the time these recommendations surfaced, several works have underlined that percutaneous gastrostomy (PEG) as well as radiologically inserted gastrostomy (RIG) may be performed in ALS patients even in the presence of respiratory failure [12,13] . Nevertheless, it has also between found that abnormal oximetry prior to gastrostomy insertion, either PEG or RIG, is a significant indicator of post-procedure survival with the worst prognosis when overnight oxymetry is abnormal [14] .…”
Section: Discussionmentioning
confidence: 99%
“…The death and complication rates were uniformly reported except in 2 studies. 31,32 The dropout rate was not specified. Additionally, none of the studies was blinded due to the intervention itself.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…3 In 2 other studies, 17 and 81 subjects used NIV without indication of daily hours of use. 31,33 In 3 other studies, there was no information concerning NIV utilization, 36 nor was it clear whether it was used routinely and/or during the PEG/RIG/PRG procedure. 37,38 The most common inclusion criteria for each study were diagnoses of amyotrophic lateral sclerosis according to El Escorial criteria, dysphagia, nutritional intake, weight loss of Ͼ 5-10%, FVC Ͻ 50%, the ability to cooperate and give consent, and aspiration.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation